2020
DOI: 10.1002/jso.25984
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tumor regression grade on recurrence after preoperative chemoradiation and gastrectomy for gastric cancer

Abstract: Background and Objectives It is unknown whether the degree of response to preoperative therapy correlates with locoregional recurrence (LR) or distant recurrence (DR) after resection of gastric cancer. Methods Patients who underwent resection of gastric adenocarcinoma following chemotherapy and chemoradiation (1995‐2015) were reviewed. The tumor regression grade (TRG) was defined by the percentage of viable tumor cells in the specimen (TRG0 = 0%; TRG1 = 1%‐2%; TRG2 = 3%‐50%; TRG3 ≥ 50%). The relationships amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…At present, the role of the TRG in predicting prognosis is controversial and inconclusive. Stark et al (21) reviewed 247 patients with gastric adenocarcinoma who received chemotherapy or chemoradiotherapy combined with surgical resection and found that the TRG was not associated with recurrence-free survival (RFS), local recurrence (LR), or distant recurrence (DR) by using the percentage of surviving tumor cells in the specimen to represent the TRG. Furthermore, Blackham et al conducted a TRG study on 58 GC patients from two institutional databases and also found that TRG was not an independent factor affecting the survival prognosis of patients (11).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the role of the TRG in predicting prognosis is controversial and inconclusive. Stark et al (21) reviewed 247 patients with gastric adenocarcinoma who received chemotherapy or chemoradiotherapy combined with surgical resection and found that the TRG was not associated with recurrence-free survival (RFS), local recurrence (LR), or distant recurrence (DR) by using the percentage of surviving tumor cells in the specimen to represent the TRG. Furthermore, Blackham et al conducted a TRG study on 58 GC patients from two institutional databases and also found that TRG was not an independent factor affecting the survival prognosis of patients (11).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the currently limited preoperative therapies and the limited number of responsive patients, findings on the value of TRG prognostic systems in LAGC are varied. Additional complexities arise when the study contexts are based on different TRG systems, especially on the comparison between TRG and ypTNM systems as independent predictors of patients survival[ 24 - 29 ]. Becker et al [ 16 ] investigated 480 patients with LAGC undergoing surgical resection and found TRG 2-3 grade (10%-100% residual tumor) to be an independent risk factor for patient OS; this reinforced the efficacy of the Becker TRG system.…”
Section: Discussionmentioning
confidence: 99%
“…This study applied the National Comprehensive Cancer Network (NCCN) classification system to assess the tumor regression grade (TRG). TRG was defined by the percentage of viable cancer cells in the resected primary tumor: TRG 0 = complete response, no viable tumor cells including lymph nodes; TRG 1 = near complete response, single cancer cells or rare small groups of cells; TRG 2 = partial response, residual tumor cells with obvious tumor regression but the amount of cancer cells is more than that in TRG 1; TRG 3 = poor or no response, extensive residual cancer with no evident tumor regression [ 13 , 14 ]. According to previous studies, pathological response was defined as TRG = 0 or 1 [ 15 ].…”
Section: Methodsmentioning
confidence: 99%